LincRNA‐p21 exon 1 expression correlates with Cdkn1a expression in vivo. (30th November 2021) - Furuhata, Riki; Imasaka, Mai; Sugimoto, Michihiko; Yoshinobu, Kumiko; Araki, Masatake; Araki, Kimi
Abstract: LincRNA ‐ p21 is a long intergenic non‐coding RNA (LincRNA) gene reported to activate the transcription of the adjacent Cdkn1a ( p21 ) gene in cis . The importance of the enhancer elements in the LincRNA ‐ p21 gene region has also been reported; however, the involvement of the LincRNA ‐ p21 transcripts in regulating Cdkn1a in vivo is still unclear. In this study, we used a LincRNA ‐ p21 ‐trapped mouse line ( LincRNA ‐ p21 Gt ) in which βgeo was inserted into intron 1, and all enhancer elements were retained. In LincRNA ‐ p21 Gt/Gt mice, the transcription of LincRNA ‐ p21 was repressed due to the βgeo sequence, and the expression of exon 1 of LincRNA ‐ p21 was restored through its deletion or replacement by another sequence, and Cdkn1a expression was also upregulated. Furthermore, regardless of the full‐length transcripts, the expression of Cdkn1a correlated with the transcription of the exon 1 of LincRNA ‐ p21 . This result indicates that the LincRNA ‐ p21 transcripts are not functional, but the transcriptional activity around exon 1 is important for Cdkn1a expression. Abstract : In this study, we used a LincRNA‐p21 ‐trapped mouse line to evaluate the functionality of the LincRNA‐p21 transcripts in vivo. As a result, we found that LincRNA‐p21 transcripts are not functional, but the transcriptional activity around exon 1 is important for Cdkn1a expression.